MODELLING KARST DENUDATION ON A SYNTHETIC LANDSCAPE - Kaufmann G.; Braun J. (My University, 2001)
This contribution presents the results of a numerical study of karst denudation on limestone plateaux. The landscape evolution model used incorporates not only long-range fluvial and short-range hill-slope processes, but also large-scale chemical dissolution of limestone surfaces. The relative efficiencies of fluvial and chemical processes are of equal importance to the landscape evolution of a plateau dropping to sea level along an escarpment. While fluvial processes have an impact confined mostly to river channels, the karst denudation process is more uniform, removing material also from the plateau surface. The combined effect of both processes results in a landscape evolution almost twice as effective as the purely erosional evolution of an insoluble landscape.